Comparative toxicity and sublethal effects of emamectin benzoate, lufenuron and spinosad on Spodoptera littoralis Boisd. (Lepidoptera: Noctuidae). (January 2015) - El-Sheikh, El-Sayed A.
Abstract: Bioassay experiments to investigate the comparative effectiveness of some new insecticides including emamectin benzoate, lufenuron, and spinosad were performed on 3rd and 5th larval instars of Spodoptera littoralis . Time–mortality relationships, effects on larval weight gain, feeding damage, and larval development of S . littoralis were also determined. The current study indicated that emamectin benzoate is the most potent among the tested insecticides on 3rd and 5th larval instars of S . littoralis with chronic LC90 values of 0.31 and 0.64 μg ml −1, respectively. The combined effect of emamectin benzoate and lufenuron or spinosad was either additive or antagonistic, suggesting that single application of these insecticides is more effective than in combination. In comparison to lufenuron and spinosad, emamectin benzoate killed both 3rd and 5th instars of S . littoralis significantly faster, markedly decreased 3rd instar larval weight gain and feeding damage, and caused 100% mortality of 5th instar during larval development. These findings suggest that emamectin benzoate is an effective compound compared with lufenuron and spinosad for control of S . littoralis . Field experiments of these insecticides might be useful to confirm a reduction in plant damage due to S . littoralis infestation. Highlights: Emamectin benzoate is more potent on Spodoptera littoralis than lufenuron or spinosad. Emamectin benzoate kills S . littoralis larvae faster than lufenuron or spinosad. Larval weight gain significantly affected by sublethal exposure to emamectin benzoate. Emamectin benzoate reduces feeding damage and negatively affects larval development.